The impact of psychostimulant use on office based buprenorphine treatment retention - Ryan Edgerton; Peter Rebeiro; Sam MacMaster; Lisa Bell; Parul Patel; Loren Ginn; Kyra Beach; Veeraj Shah; R. Lyle Cooper (Harm Reduction Journal)
Abstract Background Over a million people have died from overdose since 1999, over 600,000. of which involved opioids. Treatment options that focus on overdose prevention are desperately needed and buprenorphine treatment is a form of opioid prevention if provided in a harm reduction setting. Co-morbid opioid and stimulant use disorders have increased at a higher rate than other co-morbid combinations between 2011 and 2019. The objective of this study was to identify the effects of psychostimulant use on buprenorphine treatment retention. Methods We conducted an analysis of a cohort of 143 individuals with opioid use disorder that initiated treatment in a low-threshold, urban office based opioid treatment (OBOT) clinic located in Nashville Tennessee between 2018 and 2020. Retention was measured at 1, 3, and 6-months. Logistic regression was used to identify differences between people who tested positive for stimulants and people who did not. Results The majority of the patients were white (83%), male (64%), unhoused (59%) and uninsured (70%). There was moderate psychostimulant use in the sample with 19% testing positive for cocaine and 13% testing positive for methamphetamine at baseline. Patients testing positive for cocaine prior to their six month retention point had 0.279 lower odds of being retained in treatment. Further, testing positive for either cocaine or methamphetamine resulted in 0.284 and 0.258 odds of retention at 3 and 6-months respectively. Conclusion This study examined the impact of stimulant use on retention in buprenorphine treatment within a low-threshold OBOT clinic. Our findings differ from previous research that reported significant decreases in retention among methamphetamine users. Instead, results suggest that patients using psychostimulants can be effectively retained in care within a low-resource, low-threshold setting, though increased clinical engagement may be beneficial for those testing positive for cocaine or methamphetamine. Given the limited access to buprenorphine treatment, these findings underscore the urgent need for expanded, accessible treatment models that can effectively serve individuals with co-occurring stimulant use.